Money and Collateral - Singh, Manmohan (IMF Working Papers; Working Paper ;, 2012)
Between 1980 and before the recent crisis, the ratio of financial market debt to liquid assets rose exponentially in the U.S. (and in other financial markets), reflecting in part the greater use of securitized assets to collateralize borrowing. The subsequent crisis has reduced the pool of assets considered acceptable as collateral, resulting in a liquidity shortage. When trying to address this, policy makers will need to consider concepts of liquidity besides the traditional metric of excess bank reserves and do more than merely substitute central bank money for collateral that currently remains highly liquid.